STRATEGI KOMUNIKASI VISUAL DALAM KAMPANYE SOSIAL TENTANG INSEKURITAS DAN SEKSUALITAS REMAJA PEREMPUAN: VISUAL COMMUNICATION STRATEGY IN SOCIAL CAMPAIGN ON FEMALE ADOLESCENT INSECURITY AND SEXUALITY - Tanaya Anggita Prahastuti; Setyanto, Daniar Wikan (Jurnal Dimensi Seni Rupa dan Desain, 2025)
The increasing phenomenon of premarital sex among teenage girls is a complex social issue influenced by shifting cultural values and the pervasive use of social media. Feelings of insecurity often drive adolescents to seek external validation, particularly from the opposite sex, increasing the risk of unhealthy sexual behavior. This study aims to design a Public Service Announcement (PSA) campaign that encourages teenage girls to build self-confidence without relying on external approval. The research employs a qualitative approach through literature studies and in-depth interviews with relevant sources. The visual design process follows Robin Landa’s method, which includes brainstorming, creative strategy, concept development, sketching, digital execution, and design evaluation. The design is limited to posters and digital platforms such as Instagram and TikTok, which are widely used by the target audience. The analysis shows that a PSA with engaging visuals, simple messages, and an emotional approach can raise teenagers’ awareness of the negative impacts of premarital sex and the importance of developing self-confidence. The conclusion recommends using interactive digital media as an effective communication strategy to reach adolescents more broadly.